Understanding the interaction between energetic ions and freestanding graphene towards practical 2D perforation. Issue 15 (4th April 2016) - Buchheim, Jakob; Wyss, Roman M.; Shorubalko, Ivan; Park, Hyung Gyu
Abstract : We report experimentally and theoretically the behavior of freestanding graphene subjected to bombardment of energetic ions, investigating the capability of large-scale patterning of freestanding graphene with nanometer sized features by focused ion beam technology. Abstract : We report experimentally and theoretically the behavior of freestanding graphene subjected to bombardment of energetic ions, investigating the capability of large-scale patterning of freestanding graphene with nanometer sized features by focused ion beam technology. A precise control over the He + and Ga + irradiation offered by focused ion beam techniques enables investigating the interaction of the energetic particles and graphene suspended with no support and allows determining sputter yields of the 2D lattice. We found a strong dependency of the 2D sputter yield on the species and kinetic energy of the incident ion beams. Freestanding graphene shows material semi-transparency to He + at high energies (10–30 keV) allowing the passage of >97% He + particles without creating destructive lattice vacancy. Large Ga + ions (5–30 keV), in contrast, collide far more often with the graphene lattice to impart a significantly higher sputter yield of ∼50%. Binary collision theory applied to monolayer and few-layer graphene can successfully elucidate this collision mechanism, in great agreement with experiments. Raman spectroscopy analysis corroborates the passage of a large fraction of He + ions across graphene without much damaging the lattice whereas several colliding ions create single vacancy defects. Physical understanding of the interaction between energetic particles and suspended graphene can practically lead to reproducible and efficient pattern generation of unprecedentedly small features on 2D materials by design, manifested by our perforation of sub-5 nm pore arrays. This capability of nanometer-scale precision patterning of freestanding 2D lattices shows the practical applicability of focused ion beam technology to 2D material processing for device fabrication and integration.